PENGENAAN PAJAK PENGHASILAN PASAL 26 ATAS WAJIB PAJAK LUAR NEGERI - M. Afif Harahap; Amanda Kartika; Sefvira Maharani (INTERNATIONAL, Journal of Sharia Business Management, 2026)
Income Tax (PPh) Article 26 is a tax imposed on income received or accrued by Foreign Taxpayers (WPLN) from sources in Indonesia. This provision is regulated by Law Number 36 of 2008 concerning Income Tax. The purpose of imposing Income Tax Article 26 is to provide fairness in taxation and increase state revenue from cross-border transactions. In practice, Income Tax Article 26 is imposed on various types of income such as dividends, interest, royalties, rent, and service fees at a general rate of 20% of the gross amount. The withholding tax mechanism is carried out by domestic parties making payments to WPLN using a withholding tax system. However, this rate can be lower if there is a Double Taxation Avoidance Agreement (P3B) between Indonesia and a partner country. Therefore, understanding the subject, object, rate, and withholding mechanism of Income Tax Article 26 is crucial to support tax compliance and optimize state revenue.